PEMBANGKIT LISTRIK TENAGA SURYA PADA PROYEK PENGADAAN AIR BERSIH DESA BATAS - Fahrizal - (Jurnal APTEK, 2010)
Solar power (SP) is a new technology that is environmentally friendly and have an unlimited source location especially Indonesia, which is at the equator is highly disadvantaged because there is sunshine all year round. It is therefore a very potential new technology is developed on a large - scale in Indonesia that is being suffered an energy crisis. Starting from the problem above, the authors raise and interested at all about Solar Power as a potential energy source is developed in Indonesia, the Batas Village Water Supply Project the use of technology Solar Power Generation.